A general modal frequency-domain vortex lattice method for aeroelastic analyses. (November 2020) - Parenteau, Matthieu; Laurendeau, Eric
Abstract: The generalized aerodynamic force (GAF) matrix is derived for the Unsteady Vortex Lattice Method (UVLM) without the assumption of out-of-plane dynamics. As a result, the approach naturally includes in-plane motion and forces unlike the doublet lattice method (DLM). The derived UVLM GAF is therefore applicable to industry-standard techniques for aeroelastic stability analyses, such as the p–k method. In this work, the fluid–structure interpolation is performed with radial basis functions for surface interpolation. The generalized aerodynamic forces computed with the UVLM are verified against the DLM from NASTRAN on a simple flat plate configuration. The ability of the UVLM to include steady loads is verified with a T-tail flutter case and the results confirm the importance of including steady loads for T-tail flutter analysis. The modal frequency domain VLM therefore provides the same level of efficiency and accuracy than the DLM, but without the restrictions and with the ability to handle complex geometries. It is therefore a viable replacement to the DLM. Highlights: The approach is compatible with standard industry techniques for stability analysis. The proposed method naturally incorporates 3D kinematics. The inclusion of in-plane motion and steady loading allow accurate T-tail analyses.